2021
DOI: 10.1107/s2059798321010056
|View full text |Cite
|
Sign up to set email alerts
|

The structure of natively iodinated bovine thyroglobulin

Abstract: Thyroglobulin is a homodimeric glycoprotein that is essential for the generation of thyroid hormones in vertebrates. Upon secretion into the lumen of follicles in the thyroid gland, tyrosine residues within the protein become iodinated to produce monoiodotyrosine (MIT) and diiodotyrosine (DIT). A subset of evolutionarily conserved pairs of DIT (and MIT) residues can then engage in oxidative coupling reactions that yield either thyroxine (T4; produced from coupling of a DIT `acceptor' with a DIT `donor') or tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…While this work was in revision, Kim et al reported the structure of natively iodinated bovine thyroglobulin 35 . Interestingly, they observed three modified tyrosines with additional densities in their structure, indicative of acceptor sites: Y24 (T 4 ), Y2041 (DIT), and Y2575 (T 4 ) (Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 91%
“…While this work was in revision, Kim et al reported the structure of natively iodinated bovine thyroglobulin 35 . Interestingly, they observed three modified tyrosines with additional densities in their structure, indicative of acceptor sites: Y24 (T 4 ), Y2041 (DIT), and Y2575 (T 4 ) (Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 91%
“…When the same samples were analyzed under denaturing conditions by nonreducing SDS-PAGE—although the molecular masses of cog-Tg-L2263P, rdw-Tg-G2298R, and WT-Tg are identical—the mobility of WT-Tg still appeared slightly faster ( Fig. 1 C ), suggesting a more tightly disulfide-linked structure ( 29 , 30 ). Moreover, in WT thyroid glands, nearly all Tg proteins had migrated out of the ER so that most glycans on those Tg molecules were processed to complex sugars resistant to digestion with endoglycosidase H ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…While this work was undergoing peer review, a paper was published describing a cryo-EM structure of native bovine TG with nascent thyroid hormone present at hormonogenic sites A and B 9 . The structural organization of the region encompassing site B is essentially identical to that reported here.…”
Section: Discussionmentioning
confidence: 99%